FORMATION OF YIELD STRUCTURE ELEMENTS IN DIFFERENT VARIETIES OF WINTER WHEAT DEPENDING ON GROWING CONDITIONS - Yerashova, M. V. (Scientific Progress & Innovations, 2021)
The article presents the analysis results of yield structure elements of Kokhanka, Misiya Odeska and Pylypivka winter wheat varieties, which were sown after black fallow (at the background of pre-sowing application of N30P60K30 complete fertilizer) and after spring barley (N60P60K30) with further crops additional fertilizing with N60 locally after both predecessors at the end of plants tillering phase. The research was conducted in 2016–2018 at the State Enterprise “Experimental Farm “Dnipro” affiliated with the State Establishment “Institute of Grain Crops of the NAAS” in the crop rotation chain of black fallow – winter wheat – spring barley – winter wheat. It was established that during all the years of the research after black fallow, in comparison with crops after spring barley, such indicators as plant height and productive plant stand density were higher. Thus, during winter wheat cultivation after black fallow, the plants height in Kokhanka variety varied between 79.9–85.3 cm depending on the research year, Misiya Odeska variety – 86.2–89.0 cm; and in Pylypivka variety it was the largest – 95.7–105.6 cm. After spring barley, this indicator value according to the variety was equal to 70.0–76.1; 76.5–77.9 and 81.2–89.9 cm. Productive stems number per 1 m2 in Kokhanka variety grown after black fallow varied depending on the years of the research in the range of 561.5–643.0 pcs., in Misiya Odeska variety – 507.2–612.6, and in Pylypivka variety – 556.6– 644.5 pcs. After stubble predecessor, the values of this indicator decreased by 139.5–249.3 pcs.; 72.7– 204.0 pcs.; and 72.7–204.0 pcs., respectively, depending on the variety. According to the experimental data, in 2016, as compared with other years, winter wheat plants after both predecessors formed the largest number of grains in the ear (up to 33.9–43.6 pcs. after black fallow and 39.5–50.0 pcs. after spring barley), but thousand-kernel weight was the lowest, especially after non-fallow predecessor (27.9–33.9 g). On the whole, in 2016, the maximum indicators of biological yield were formed; they amounted to 730.9–855.1 g/m2 after black fallow, depending on the variety, and 564.5–653.3 g/m2 after spring barley. At cultivating winter wheat after black fallow each year, different varieties prevailed in terms of biological yield. At the same time, after spring barley, the best results during all years of the research were obtained when Pylypivka variety was used.